Yalla! Fresh food and more... - Al-Ajmi, Majda (2009)
The work provides a business plan for an innovative idea for a restaurant. The restaurant will be operating in Oman, Muscat under Bin Mirza International (BMI).It will provide healthy Arabic food in a modern fast-food style.